Teacher communication intensity impacts student learning motivation in the era of the industrial revolution 4.0 - Ali Akbarjono (Jurnal Konseling dan Pendidikan, 2022)
The purpose of this study was to determine whether there was an influence of the intensity of teacher communication on students' learning motivation in Islamic education learning in the industrial era 4.0 at SMP Negeri 26 Seluma. The research approach used is quantitative with associative methods through field surveys. The formulation of the problem in this study is whether there is an influence of the intensity of teacher communication on student learning motivation in the industrial era 4.0 for students of SMP Negeri 26 Seluma. Based on the results of the study, it was concluded that there was an influence of the intensity of teacher communication on student learning motivation in Islamic education learning management in the industrial era 4.0 at SMP Negeri 26 Seluma. The correlation calculation results show that the value of the "r" count is 0.472 with N = 26 at df 24 with a 5% significance level of 0.388. While the calculated rxy result of 0.472 was greater than the "r" table at a significance level of 5%, so the hypothesis which states that there is an influence of teacher communication intensity on motivation to learn Islamic Education in the industrial era 4.0 students of SMP Negeri 26 Seluma can be accepted. The intensity of teacher communication contributes to student learning motivation by 22.27% and the remaining 77.3% is determined by other variables.